West Nusa Tenggara (NTB) Provincial Governments Efforts in Obtaining and Maintaining Unqualified Opinion by the Audit Board of Indonesia - Yazied, Naufal; Djamhuri, Ali; Purwanti, Lilik (Journal of Accounting and Business Education, 2018)
This research aimed to describe the efforts of NTB provincial government in obtaining and maintaining unqualified opinion by The Audit Board of Indonesia. This research used a qualitative approach. The results of this study indicated that in obtaining an unqualified opinion, the NTB provincial government did four stages of preparation; there were strengthening the leadersâ commitment, developing policies in obtaining an unqualified opinion, following-up BPK-RIâs findings, and organizing asset management. Meanwhile, to maintain the unqualified opinion, NTB provincial government did six stages, there were increasing the leadersâ commitment, following up the findings of BPK-RI, establishing accounting policies and procedures, conducting internal control system, increasing the resources of local government officials, and developing the information system of financial and regional assets.